GAMBARAN FAKTOR FAKTOR YANG MENYEBABKAN REMAJA PUTRI UNTUK MEROKOK - Dessy Lestari (Journal of Research and Measurement in Psychology, 2017)
ABSTRACT The purpose of this research is to give a representation about teenage girls cigarette smoking factor in Jakarta. Sample for this research are 61 teenage girls with different characteristics age range 1518 years, smoking and live in Jakarta. Data collection technique is non probability sampling technique with accidental sampling. The research design used by the writer is descriptive statistical analysis. According to the results obtained from the respondents, of the three dimentions that can lead teenage girls smoking is peer influence, family influence, and self image of smokers showed that the three dimentions there are no dimention are very striking as a cause of teenage girls smoking, but from the third dimentions of peer influence reached the highest score compared with the other two dimentions with the percentage of 35%. Keywords: The factors that cause smoking, Teenage girls